Paddle boats to boost edu-tourism - Siti Sarah, Mohamad Rajimi (2017)
Universiti Malaysia Pahang (UMP) received three units of Paddle Boat in its efforts to become educational tourism hub (edu-tour) in Kuala Pahang.